Pola Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru di MTsN 2 Medan - Fauziana Lubis; Amini Amini; Syaiful Bahri (Journal on Education, 2023)
This research is a qualitative descriptive study that aims to determine the principal's leadership pattern, the relationship between the principal's leadership pattern and teacher performance, and improving teacher performance at MTsN 2 Medan through the principal's leadership pattern. The objects in this study were the principals and teachers who taught at MTsN 2 Medan. Data collection techniques using observation, interviews and documentation. Data analysis using data reduction, data presentation and conclusions. The results of the study show that: 1) The leadership pattern of the principal at MTsN 2 Medan is through a pattern of supervision and a pattern of coaching by conducting class visits with very periodic time, observation visits, academic guidance, and non-academic guidance, as well as a pattern of coaching carried out by group techniques such as meetings or conferences, group discussions, and upgrading/training; 2) Through the principal's leadership pattern which consists of a pattern of supervision and a pattern of coaching, the teacher's performance in class management has been good, where the teacher has been able to determine the right learning strategy, use fun methods for students, and is able to manage learning in the classroom as a whole, and teachers at MTsN 2 Medan have good conceptual skills, where teachers are able to balance school conditions with their own abilities to achieve real learning goals, and have four teacher competencies namely pedagogic, personality, social and professional; 3) The principal's leadership pattern through supervision and coaching can improve teacher performance at MTsN 2 Medan.